A COMPARISON OF PHYSIOLOGICAL CHANGES INDUCED BY PRONE POSITION OVER WILSON’S FRAME AND HORIZONTAL BOLSTERS IN LUMBAR SPINE SURGERY – A RANDOMIZED PROSPECTIVE STUDY - Dr. Shubham Khandelwal; Dr. Nisha Sharma; Dr. Vijay Mathur; Dr. Ravindra Sisodia; Dr. Avnish Bharadwaj; Dr. Shubhina Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: Ideal patient positioning involves balancing surgical comfort, against the risks related to the patient position. There is paucity of information on effect of prone position on blood loss and intra- abdominal pressure (IAP) and how these changes correlate with respiratory airway pressures. The study was designed to compare Wilson’s frame and horizontal bolsters to find a better technique for better intraoperative optimisation of the patient. METHODS: The study was conducted on 60 patients after obtaining approval from ethical committee. Patients were positioned prone on Wilson’s frame (W) and Horizontal bolster (H). IAP was measured in the following positions and time intervals: IAP 1 (T1) - supine after the induction after placement of Foley’s catheter; IAP 2 (T2) - 10 minutes after correct positioning of the patient in prone position; and IAP 3 (T3) - at the end of surgery, before turning the patient supine. Simultaneously, airway pressures and vitals were recorded. Blood loss was estimated at the end of surgery. RESULTS: Mean IAP was significantly higher in group W at T2 and T3 (p <0.001 each). Significantly higher airway pressuresobserved in Group W as compared to group H at T2 and T3. Blood loss in group W was significantly higher than average blood loss in group H (p = 0.006). CONCLUSIONS: The patients who were positioned prone on horizontal bolsters for lumbar surgery had significantly lower IAP, airway pressures and lesser intraoperative blood loss as compared to patients positioned on Wilson’s frame.